Current chemoprevention approaches in Lynch syndrome and Familial adenomatous polyposis: a global clinical practice survey - Mraz, Kathryn A.; Hodan, Rachel; Rodgers-Fouche, Linda; Arora, Sanjeevani; Balaguer, Francesc; Guillem, Jose G.; Jeter, Joanne M.; Kanth, Priyanka; Li, Dan; Liska, David; Melson, Joshua; Perez, Kimberly; et al. (Frontiers in Oncology, 2023)
Background International chemoprevention preferences and approaches in Lynch syndrome (LS) and APC-associated polyposis, including Familial adenomatous polyposis (FAP) and attenuated FAP (AFAP) have not been previously explored. Aim To describe current chemoprevention strategies for patients with LS or FAP/AFAP (referred to collectively as FAP) practiced by members of four international hereditary cancer societies through administration of a survey. Results Ninety-six participants across four hereditary gastrointestinal cancer societies responded to the survey. Most respondents (91%, 87/96) completed information regarding their demographics and practice characteristics relating to hereditary gastrointestinal cancer and chemoprevention clinical practices. Sixty-nine percent (60/87) of respondents offer chemoprevention for FAP and/or LS as a part of their practice. Of the 75% (72/96) of survey respondents who were eligible to answer practice-based clinical vignettes based off of their responses to ten barrier questions regarding chemoprevention, 88% (63/72) of those participants completed at least one case vignette question to further characterize chemoprevention practices in FAP and LS. In FAP, 51% (32/63) would offer chemoprevention for rectal polyposis, with sulindac - 300 mg (18%, 10/56) and aspirin (16%, 9/56) being the most frequently selected options. In LS, 93% (55/59) of professionals discuss chemoprevention and 59% (35/59) frequently recommend chemoprevention. Close to half of the respondents (47%, 26/55) would recommend beginning aspirin at time of commencement of the patient’s first screening colonoscopy (usually at age 25yrs). Ninety-four percent (47/50) of respondents would consider a patient’s diagnosis of LS as an influential factor for aspirin use. There was no consensus on the dose of aspirin (≤100 mg, >100 mg - 325 mg or 600 mg) to offer patients with LS and there was no agreement on how other factors, such as BMI, hypertension, family history of colorectal cancer and family history of heart disease, would affect the recommendation for aspirin use. Possible harm among older patients (>70 years) was identified as the most common reason to discourage aspirin use. Conclusion Although chemoprevention is widely discussed and offered to patients with FAP and LS by an international group of hereditary gastrointestinal cancer experts, there is significant heterogeneity in how it is applied in clinical practice.